2021
DOI: 10.1002/uog.23608
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester diagnosis of congenital cytomegalovirus infection after maternal primary infection in early pregnancy: feasibility study of viral genome amplification by PCR on chorionic villi obtained by CVS

Abstract: What are the novel findings of this work?Diagnosis of placental infection following maternal primary infection with cytomegalovirus (CMV) in early pregnancy, i.e. when the fetus is at risk of sequelae, can be achieved in the first trimester by chorionic villus sampling (CVS) and polymerase chain reaction amplification of the viral genome in chorionic villi, with high specificity and negative predictive value. What are the clinical implications of this work?Absence of CMV in the chorionic villi sampled by CVS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
2
13
0
1
Order By: Relevance
“…Although the diagnosis of congenital infection is made at birth and potential sequelae are assessed at 2 years of age at the earliest, we chose to consider the result of PCR analysis of amniotic fluid at 17–22 weeks' gestation as being indicative of transplacental passage of the virus. We feel this was justified because, while a negative amniotic fluid PCR result has been found to be associated with an infected neonate in up to 8% of cases, these false‐negative results were related to late transplacental passage – much later than the embryonic period – and did not yield any symptomatic forms of cCMV 16,24,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the diagnosis of congenital infection is made at birth and potential sequelae are assessed at 2 years of age at the earliest, we chose to consider the result of PCR analysis of amniotic fluid at 17–22 weeks' gestation as being indicative of transplacental passage of the virus. We feel this was justified because, while a negative amniotic fluid PCR result has been found to be associated with an infected neonate in up to 8% of cases, these false‐negative results were related to late transplacental passage – much later than the embryonic period – and did not yield any symptomatic forms of cCMV 16,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Only patients who underwent amniocentesis performed at least 8 weeks after maternal infection and from 17 weeks' gestation onwards were included. Ten of the cases reported in this series underwent chorionic villus sampling for array comparative genomic hybridization and PCR amplification of CMV-DNA and have been reported previously 8 .…”
Section: Figurementioning
confidence: 99%
“…In utero therapy using valaciclovir (8 g/day, 2 g four time a day) was progressively extended from curative (in case of infected fetuses) to preventive treatment (risk of fetal infection following PMI) [ 81 , 82 ]. Our group has recently implemented the diagnosis of fetal infection using CMV-PCR on trophoblast samples obtained by chorionic villus sampling (CVS) at 13–14 weeks [ 83 ]. Profiling of inflammatory mediators on infected trophoblast samples could provide additional data on placental immunity and on the pathophysiology of vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that viral DNA could be amplified by PCR in the trophoblast after chorion villus sampling at 13 to 14 weeks in cases that will demonstrate a positive PCR in amniotic fluid in the second trimester with good positive and negative predictive values of 100% and 91%, respectively. 40 Finally, whethe the decision to terminate the pregnancy with an infected fetus after maternal infection in the first trimester is a harmful effect of screening is debatable. Complex emotional experiences are integral to early pregnancy.…”
Section: Clinical Perspectivementioning
confidence: 99%